187k views
0 votes
HELP THIS IS DUE TOMORROW!
Algebra 2 question!
Picture attached below

HELP THIS IS DUE TOMORROW! Algebra 2 question! Picture attached below-example-1
User Nick Rice
by
5.4k points

1 Answer

2 votes

Answer:


(4+√(3))/(4)-((3+4√(3)))/(12)i

Explanation:

Given expression:


(4+√(3))/(3+√(-3))


\textsf{Apply radical rule}:\quad √(-a)=√(a)√(-1)


\implies (4+√(3))/(3+√(3)√(-1))


\textsf{Apply imaginary number rule}:\quad √(-1)=i


\implies (4+√(3))/(3+√(3)i)

Multiply by the conjugate of the denominator:


\implies (4+√(3))/(3+√(3)i) \cdot (3-√(3)i)/(3-√(3)i)


\implies ((4+√(3))(3-√(3)i))/((3+√(3)i)(3-√(3)i))


\implies (12-4√(3)i+3√(3)-√(3)i√(3))/(9-3√(3)i+3√(3)i-√(3)i√(3)i)


\implies (12+3√(3)-4√(3)i-3i)/(9-3i^2)


\implies (12+3√(3)-(3+4√(3))i)/(9-3i^2)


\textsf{Apply imaginary number rule}:\quad i^2=-1


\implies (12+3√(3)-(3+4√(3))i)/(9-3(-1))


\implies (12+3√(3)-(3+4√(3))i)/(12)

Separate the fractions:


\implies (12+3√(3))/(12)-((3+4√(3))i)/(12)

Simplify:


\implies (4+√(3))/(4)-((3+4√(3)))/(12)i

User Adelphus
by
5.4k points